Comparison of Virulence Patterns Between Streptococcus uberis Causing Transient and Persistent Intramammary Infection - Srithanasuwan, Anyaphat; Pangprasit, Noppason; Suriyasathaporn, Witaya (Frontiers in Veterinary Science, 2022)
The objectives of this study were determined by two experiments including Experiment 1 (EXP1) using Streptococcus uberis obtained from a weekly longitudinal study to compare virulence patterns between transient and persistent intramammary infection (IMI), and Experiment 2 (EXP2) using a stored-known-appearance PFGE strain of a contagious S. uberis to determine a change of virulence patterns after long-term transmission. For EXP1, quarter milk samples from 31 milking cows were aseptically and longitudinally collected once a week for 10 weeks. A total of 14 S. uberis isolates from quarters with 1 and >4 weeks of duration of IMI were categorized as transient and persistent IMI, respectively. For EXP2, 11 isolates of a stored-known-appearance PFGE strain of S. uberis from our previous study (1) were randomly selected, including 5 from transient IMI (1 month) and 6 from persistent IMI (>1 month). The virulence profiles of all isolates were investigated, including sua, hasAB, hasC, gapC, pauA, and CAMP factor or cfu, using PCR. The Kaplan–Meier estimates were used to calculate the duration of IMI in EXP1. Approximately 50% of field S. uberis IMI was spontaneously cured within 1 week, while 25% was not cured within 10 weeks. From EXP1, 4 virulence patterns were found in 14 isolates. The majority of patterns for transient S. uberis did not include hasAB (63.6%), the gene relating to capsule formation. Regardless of transient or persistent IMI, a high similarity of the virulence pattern within a PFGE strain was found in EXP2. Few changes of virulence pattern within a PFGE strain were found or were related to its subsequently changing to transient IMI.